Application of Mechanistic Modeling for Gas Lift Optimization: A General Scaling Curve for Variations of Tubing Size to Optimum Gas Injection - Prasandi Abdul Aziz; Ardhi Hakim Lumban Gaol; Wijoyo Niti Daton; Steven Chandra (Universitas Islam Riau (UIR) Press, 2019)
Gas Lift is currently held as one of the most prominent method in artificial lift, proudly operated flawlessly in hundreds of oil wells in Indonesia. However, gas lift optimization is still governed by the exhaustive Gas Lift Performance Curves (GLPC). This practice, albeit as established as it should be, does require repetitive calculations to be able to perform in life of well operations. Therefore, a new approach is introduced based on the mechanistic modeling. This research highlights the application of fundamental mechanistic modeling and its derivative, the Flow Pattern Map (FPM) for quick estimation of optimum injection gas rate, accompanied by a novel correction factor to account changing tubing sizes. It is hoped that this approach can be beneficial in developing a multitude of gas lift wells with changing tubing sizes.